2010
DOI: 10.1111/j.1365-2095.2010.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary graded levels of cottonseed meal and gossypol on growth performance, body composition and health aspects of allogynogenetic silver crucian carp, Carassius auratus gibelio♀ × Cyprinus carpio♂

Abstract: A 6‐month trial was conducted to evaluate the effects of dietary cottonseed meal (CSM) and free gossypol (FG) on allogynogenetic silver crucian carp, Carassius auratus gibelio♀ × Cyprinus carpio♂ with 4 replicates of each treatment. Isonitrogenous and isocaloric diets were formulated with the 0 g kg−1 (control), 200 g kg−1, 400 g kg−1, and 560 g kg−1 CSM. Diets with FG were made by supplementing batches of control diet with 214 mg kg−1, 428 mg kg−1, and 642 mg kg−1. Weight gain, specific growth rate, and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 32 publications
4
38
3
Order By: Relevance
“…SBM is a cost‐effective feed ingredient and constitutes up to 50% of the diet of some freshwater fish species (Yue and Zhou ), because it is an economical protein source with relatively highly digestible protein and energy contents and a suitable amino acid profile (Hertrampf and Piedad‐Pascual ). SBM was a more valuable plant protein source than either CSM or CM in blunt snout bream, because it could not be completely replaced by the two without compromising quality, a result that is consistent with similar reports in tilapia (Yue and Zhou ; Zhou and Yue ; El‐Saidy and Saad ), allogynogenetic silver crucian carp (Cai et al ), and grass carp (Zheng et al ), although grass carp have been reported to utilize CSM as well as SBM (Koprucu and Sertel ).…”
Section: Discussionsupporting
confidence: 85%
“…SBM is a cost‐effective feed ingredient and constitutes up to 50% of the diet of some freshwater fish species (Yue and Zhou ), because it is an economical protein source with relatively highly digestible protein and energy contents and a suitable amino acid profile (Hertrampf and Piedad‐Pascual ). SBM was a more valuable plant protein source than either CSM or CM in blunt snout bream, because it could not be completely replaced by the two without compromising quality, a result that is consistent with similar reports in tilapia (Yue and Zhou ; Zhou and Yue ; El‐Saidy and Saad ), allogynogenetic silver crucian carp (Cai et al ), and grass carp (Zheng et al ), although grass carp have been reported to utilize CSM as well as SBM (Koprucu and Sertel ).…”
Section: Discussionsupporting
confidence: 85%
“…CM is a valuable substitute for expensive protein sources and has been tested in some fi sh species (Cai et al, 2011). However, it is important to evaluate the eff ect of dietary CM on growing fi sh.…”
Section: Discussionmentioning
confidence: 99%
“…; Cai et al . ). Recently, we successfully determined the optimal dietary replacement levels of FM by Chlorella in crucial carp (Shi et al .…”
Section: Introductionmentioning
confidence: 97%